INOVASI TEKNOLOGI DIGITAL DALAM MENINGKATKAN KOMPETENSI PEGAWAI DISPENDUK KOTA BANDUNG (KAJIAN STUDI LITERATUR MANAJEMEN SUMBER DAYA MANUSIA) - SEPTIAN, DIAN (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2023)
This journal explores the role of digital technology innovation in enhancing the competence of employees at the Civil Registry and Civil Registration Office of Bandung City. The Bandung City Government has actively embraced digital technology in various aspects of public services, including human resource management. We analyze the impact of digital technology innovation on employee competence in the context of government regulations, including Law Number 23 of 2014 concerning Regional Government and Government Regulations related to civil servant management. Through an in-depth literature review, we identify key concepts related to the implementation of digital technology in human resource management. The research findings reveal that digital technology innovation can significantly improve employee competence, streamline administrative processes, and enhance efficiency within the Civil Registry and Civil Registration Office of Bandung City. This study holds significant implications for improving public services and government organizational effectiveness. Our findings can serve as a foundation for further strategy development in the adoption of digital technology in human resource management in the government sector. As a result, it is expected that public services will become more efficient and of higher quality, while employees will have greater opportunities to develop their competencies